It’s a Man’s Job: Income and the Gender Gap in Industrial Research - Hoisl, Karin; Mariani, Myriam (Management Science, 2017)
This study examines differences in income and job performance between women and men in creative, highly skilled jobs tasked with achieving technological inventions. By building on data pertaining to 9,692 inventors from 23 countries, this study shows that female inventors represent only 4.2% of total inventors, and they earn about 14% less than their male peers. The gap persists even when controlling for sources of heterogeneity, the selection of inventors into types of jobs and tasks, and potential parenthood, instrumented by exploiting a source of variation related to religious practices. The income gap is not associated with differences in the quality of the inventions that female and male inventors produce. Thus, even in this human capital–intensive profession, where capabilities and education are important assets, and productivity differentials can be observed, women earn less than men, though they contribute to the development of high-quality inventions as much as men do. This paper was accepted by Lee Fleming, entrepreneurship and innovation.